Factores psicosociales del consumo de sustancias psicoactivas en jóvenes de un barrio del municipio de Uribia - Rodríguez González, Arleth Yiseth (Universidad Antonio Nariño, 2022)
The research entitled Psychosocial factors of the consumption of Psychoactive Substances in young people of a neighborhood of the municipality of Uribia was carried out, which had as a general objective, to describe the psychosocial factors associated with the use of SPA, perceived by the young people of a neighborhood of the municipality of Uribia La Guajira. It was decided to work with these variables because the scourge of the consumption of psychoactive substances in Colombia is an inexhaustible issue because around it the lives of hundreds of Colombian families are interwoven that in one way or another have a close relationship with the issue, otherwise There is a relative, even distant, there are links in the área of marketing drugs or in some way in the processing of the same.